Combined thermobarometry and geochronology of peraluminous metapelites from the Karakoram metamorphic complex, North Pakistan; New insight into the tectonothermal evolution of the Baltoro and Hunza Valley regions - Palin, R (Blackwell Publishing/ Wiley, 2012)
Petrographic analysis of peraluminous metapelites from two separate regions of the Karakoram metamorphic complex, North Pakistan, has produced new insights into the P-T evolution of the deep crust along the south Asian margin before and after the India-Asia collision. Average PT estimates and pseudosection construction in the (MnNCKFMASHTO) system using THERMOCALC have provided prograde and peak metamorphic conditions and UPb geochronology of metamorphic monazite has provided age constraints. Two new events in the tectonothermal evolution of the Hunza Valley have been documented; an andalusite-grade contact metamorphic event at 105.5 ± 0.8 Ma, at unknown P–T conditions, associated with the widespread subduction-related granite magmatism before the India-Asia collision, and a kyanite-grade overprint of sillimanite-grade rocks with peak P–T conditions of 7.8 kbar, 645 C at 28.2 ± 0.8 Ma associated with the ongoing India-Asia collision. A kyanite-grade event observed in the Baltoro region with similar peak P–T conditions (7.4–8.0 kbar, 640–660 C) is interpreted to have occurred sometime after 21.8 ± 0.6 Ma, however, previous studies have suggested that this event commenced in the Baltoro as early as c. 28 Ma. A calculated prograde P–T path for this kyanite-grade event in the Baltoro indicates that garnet first nucleated on an initially high geothermal gradient (30 C/km) and grew during a significant increase in pressure of 2.6 kbar over a temperature increase of 100 C. This event is thought to represent evidence for conductive heating of the middle crust during early stages of intrusion and lateral migration of the Baltoro batholith, with thermal conditions comparable with tectonic models of magmatic over-accretion.